2023
DOI: 10.3389/fmicb.2023.1101150
|View full text |Cite
|
Sign up to set email alerts
|

A nostoxanthin-producing bacterium, Sphingomonas nostoxanthinifaciens sp. nov., alleviates the salt stress of Arabidopsis seedlings by scavenging of reactive oxygen species

Abstract: A novel, nostoxanthin-producing, endophytic bacterium, designated as AK-PDB1-5T, was isolated from the needle-like leaves of the Korean fir (Abies koreana Wilson) collected from Mt. Halla in Jeju, South Korea. A 16S rRNA sequence comparison indicated that the closest phylogenetic neighbors were Sphingomonas crusticola MIMD3T (95.6%) and Sphingomonas jatrophae S5-249T (95.3%) of the family Sphingomonadaceae. Strain AK-PDB1-5T had a genome size of 4,298,284 bp with a 67.8% G + C content, and digital DNA–DNA hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 83 publications
0
13
0
Order By: Relevance
“…Similar previous studies showed that, when externally applied via foliar spray, β-carotene can alleviate salt stress by reducing the amount of hydrogen peroxide (H 2 O 2 ) which can increase the ROS contents ( Babaei et al, 2022 ). Additionally, bacteria that produce nostoxanthin have been found to reduce ROS-induced stress in plants and facilitate plant growth when exposed to salinity stress ( Jiang et al, 2023 ). β-carotene is a member of the carotenoid family, a well-known group of isoprenoid pigments extensively researched for their ability to quench ROS and plant self-defense mechanisms, ultimately mitigating oxidative stress-induced damage ( Li et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar previous studies showed that, when externally applied via foliar spray, β-carotene can alleviate salt stress by reducing the amount of hydrogen peroxide (H 2 O 2 ) which can increase the ROS contents ( Babaei et al, 2022 ). Additionally, bacteria that produce nostoxanthin have been found to reduce ROS-induced stress in plants and facilitate plant growth when exposed to salinity stress ( Jiang et al, 2023 ). β-carotene is a member of the carotenoid family, a well-known group of isoprenoid pigments extensively researched for their ability to quench ROS and plant self-defense mechanisms, ultimately mitigating oxidative stress-induced damage ( Li et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…ROS in plant roots were detected using DCFH-DA (Sigma, Korea) as previously described ( Jiang et al, 2023 ), but with a minor modification. Briefly, the seedlings were exposed to 5 μM DCFH-DA in 50 mM sodium phosphate buffer (pH 7.0) for 30 min in the dark.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their potential usefulness, coral-associated carotenoid-producing bacteria have not been deposited in public repositories, and their general unavailability hinders progress in coral conservation research. Although carotenoid-producing bacteria have been isolated from seawater (Hameed et al 2012; Yokoyama et al 1994; Jiang et al 2023), it remains unclear whether seawater-derived bacteria can be used as probiotics.…”
Section: Introductionmentioning
confidence: 99%
“…59 The effective publication states that the type strain was also deposited as CIP 109896, but no documentation was supplied. 60 The effective publication states that the type strain was also deposited as CIP 110370, but no documentation was supplied.…”
mentioning
confidence: 99%